Biohydrogen production from Palm Oil Mill Effluent (POME) in an anaerobic hybrid bioreactor / Parviz Mohammadi - Parviz, Mohammadi (2012)
The effects of various pretreatment methods on the enrichment of H2 evolving bacterial population and their hydrogen production efficiency using palm oil mill effluent (POME) as substrate were studied. Heat shock pretreatment was shown to be the most effective in enhancing the biological H2 production. Up-flow anaerobic sludge blanket fixed film (UASB-FF) bioreactor is a modern bioreactor and was used to generate of biological hydrogen with the help of granulated microbial aggregates. A lab scale UASB-FF bioreactor (2.55 lit) with an external settling tank was successfully designed and operated for biohydrogen production from POME. The use of packing media in the middle portion reduced loss of biomass due to flotation associated with poorly performing UASB reactors. The bioreactor was developed in order to shorten the start-up period at low hydraulic retention time (HRT). The organic loading was gradually increased from 4.68 to 51.8 g COD/l.d during this period. Granular sludge was found to develop rapidly within 22 days with an increase in size of granules from an initial pinpoint size to about 1 mm. A marked improvement in shortening reactor start-up period (22 days) was achieved with 42.5 % COD removal at an OLR of 51.8 g COD/l.d. Experiments of fermentation hydrogen production of POME were conducted based on a central composite face-centered design (CCFD) and modeled and analyzed with two variables i.e. feed flow rate (QF) and up-flow velocity (Vup) using response surface methodology (RSM). The optimum conditions for the fermentation hydrogen production of the pre-settled POME were between QF of 3.71 l/d, Vup of 1.48 m/h and QF of 2.03 l/d, Vup of 2.31m/h, respectively. The experimental findings were in close agreement with the model prediction. The proposed kinetic equations and a simplified Monod’s model were successfully employed to describe the kinetics of fermentation hydrogen production from POME in the UASB-FF bioreactor. The maximum hydrogen production rate and hydrogen yield were 0.306 l H2/g CODremoved.d and 0.310 l H2/g COD, respectively. The maximum specific growth rate (μmax) of hydrogenesis bacteria grown on POME as substrate, the half-velocity constant (Ks), were calculated at 0.371 d-1 (38 °C) and 10.9 g/L, respectively, when POME concentration was 15.0 g/L. In this study, the kinetic parameters Y, Kd, and k were obtained 0.093 g/g, 0.0046 d-1, and 3.99 g COD/g VSS.d, respectively. In a batch experiment, Effects of three important variables viz. initial COD concentration (CODin), biomass concentration and initial bicarbonate alkalinity (BA) on biological hydrogen production from POME using the granulated sludge were also investigated. The maximum specific hydrogen production rate (55.42 mmol H2/g VSS.d) was at the CODin, MLVSS and initial BA of 6500 mg/l, 2000 mg/l and 1100 mg CaCO3/L, respectively. The maximum hydrogen yield (124.5 mmol H2/g CODremoved) was also occurred at the CODin, MLVSS and initial BA of 3000 mg/l, 4000 mg/l and 1100 mg CaCO3/L, respectively. The minimum initial bicarbonate alkalinity required was determined to be 0.17 g CaCO3 per gram initial COD. The results of mass transfer study demonstrated that substrate mass transfer into granules was not a limiting factor in POME anaerobic fermentation by the microbial granules. All cumulative hydrogen production was well correlated to the modified Gompertz equation with R2 more than 0.99. The kinetic parameters for total accumulated hydrogen production (ml) were P: 329.8 ml, Rmax: 83.5 ml H2/h and λ: 5.45 h.